2010
DOI: 10.1111/j.1745-4514.2009.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

WATER EXTRACTS FROMNELUMBO NUCIFERALEAF REDUCED PLASMA LIPIDS AND ATHEROSCLEROSIS IN CHOLESTEROL-FED RABBITS

Abstract: Nelumbo nucifera Gaertn (Nelumbonaceae) leaf was used as food or beverage in Taiwan. Recently, the leaf extract was also found to possess antioxidative ability. Base on the close relationship between antioxidation and atherosclerosis, we investigated the inhibitory activity of the water extract (Nelumbo nucifera leaf extract [NLE]) on hyperlipidemia and atherosclerosis. In rabbits fed with high‐cholesterol diet (HCD) plus 0.5% or 1.0% of NLE, the inhibitory level of triglyceride was 30% and 46.6%, and low‐dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Importantly, the concentration of NLE (0.5%), which was established according to the findings of previous chemopreventive studies . Oral NLE has been shown to prevent malignancy in MCF‐7 breast cancer cell xenografts and in vitro and to reduce body lipid accumulation in the high‐cholesterol diet (HCD)‐induced obesity . Our study demonstrated that NLE administration attenuated DEN‐induced oxidative stress and the inflammatory response and abrogated the formation of preneoplastic liver nodules and the development of HCC.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Importantly, the concentration of NLE (0.5%), which was established according to the findings of previous chemopreventive studies . Oral NLE has been shown to prevent malignancy in MCF‐7 breast cancer cell xenografts and in vitro and to reduce body lipid accumulation in the high‐cholesterol diet (HCD)‐induced obesity . Our study demonstrated that NLE administration attenuated DEN‐induced oxidative stress and the inflammatory response and abrogated the formation of preneoplastic liver nodules and the development of HCC.…”
Section: Discussionmentioning
confidence: 63%
“…Several studies have shown that NLE exerts cancer chemopreventive efficacy in a wide variety of rodent models of carcinogenesis . The concentrations of NLE required eliciting biochemical changes germane to chemoprevention in experiments in vitro are in the 0.5 to 3.0 mg/ml range . For the development of NLE as a potential liver cancer chemopreventive agent in vivo, we select a safe dose of 0.5–1% (based on administration with food) is appropriate for daily supplements, might elicit chemoprevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations